IoT based design and implementation of WSN smart home automation intelligent system using flask web server - Mallikharjuna Rao, G. (International Journal of Engineering and Technology, 2019)
The smart home is changing the way we live today, in this project we introduce to automate the entire home appliances using wireless sensor network to control and monitor the connectivity and communication using Raspberry Pi. The Raspberry Pi is used as central coordinator to connect with four NodeMCU wirelessly operating under star network topology, to handle the home appliances. The Raspberry Pi and NodeMCU modules are connected to the internet using the hotspot. The coordinator is monitored and controlled through HTTP web page protocol. The web page is developed using HTML, CSS, JavaScript, and chart.js. The website hosted on the flask web server, through the webpage automation system control the internet through Wi-Fi module, it makes a complete setup of home automation using the Internet of Things. Finally, the entire core design of hardware and software is developed to manage the home appliances through a Flask web server is done in local storage, can be viewed in a web browser using the client-server model.Â